ترقية استيعاب المفردات لدى الطلاب باستخدام طريقة التدريبات (Drill Method) للصف الأول في المرحلة المتوسطة بمعهد الإمام النَّووي لابوهن باتو سومطرى الشمالية (البحث صفي إجرائي) - Halimah, Putri; Damanik, Wagiman; Ulum, Bahrul (Cahaya Ilmu Bangsa Institute, 2025)
This research is based on the low level of mastery of mufradat, some students find it difficult during the learning process, this is caused by the students' lack of desire and enthusiasm in this lesson. This research aims to improve students' mastery of mufradat by using the drill method. The research method used in this research is classroom action research using two cycles. Data collection techniques used in this research were observation, interviews and tests. The research results were obtained from the results of comparative analysis from the first cycle and the second cycle. The average in the first cycle reached 63.58 or 21% (6 people) of students who completed and 79% (23 people) of students did not pass. and increased in the second cycle reaching an average of 80.13 and 72% (21 people) students who passed and 28% (8 people) students who did not pass. It can be concluded that this drill method can improve the mastery of mufradat of class VII students at the Imam An-Nawawy Labuhan Batu Islamic Boarding School.